Cyberfeminis: Wajah Baru Pembebasan Diri Kaum Perempuan - Trisna Andarwulan (Kafa`ah: Journal of Gender Studies, 2017)
Feminists appear to be a movement to reject everything being  marginalized, subordinated, and demeaned by dominant cultures, either in politic, economic, culture, or social life. The purpose of this research is to describe new face of the women rebellation. Library research was employed where the data taken from content analysis. The research finding showed that one of the new movements done by feminists in the era of globalization is through the virtual world, the cyber world. This movement became known as cyberfeminists. Its 'cross-boundary nature' which beyond the physical and geographical world as a new social field for feminists to explore new freedoms in term of building their relationships and identities. One of the common movement is by using the publication of short stories and novels published in cyberspace. 'Run Away with You' is one of the short stories reviewed in this study.